Memorial de uma profissão: a historiografia do Serviço Social em Portugal - Vale, Camile Biscola do (2021)
The research undertaken aimed to present the history of Social Work in Portugal through the narration of the memory of Portuguese social workers who contributed, with their professional action, to academic, intellectual development, and to the struggle for the consolidation and recognition of Social Work in the Portuguese society. The testimonies recorded here are experiences of those who constituted and still are part of the history of the profession on a daily basis, in order to complement the official historiography. The theoretical and methodological background of the thesis was based on the dialectical historical materialism, from the perspective of Walter Benjamin, adopting the method of Benjamin historiography, which allows us to know the past from the human experience and, from that, to have knowledge of the history from its relations and articulations with the historical movement, thus making it possible to recover the history of Social Work not only to learn about the past, but also as a way to understand the present and new challenges in the future, preserving it through new archives – Professional Memorials. To this aim, three social workers were interviewed, teachers of the Social Work course in Portugal, selected from an academic section, linked to training in the country's first Social Work schools (Lisbon, Porto and Coimbra), and to participation in the first Master's degree in Social Work in Portugal, carried out through a partnership between the Social Service Institute of Lisbon (ISSSL) and the Pontifical Catholic University of São Paulo (PUC-SP), through a Cooperation Protocol between countries. Based on qualitative research, a bibliographic survey was carried out to support the theory and distinguish the concepts between history and memory, as well as the main aspects of the historiography of Social Work in Portugal, since the Oral History Methodology was used to record the narratives, aiming to preserve the originality of reproduction at the time of transcription. From the record of the narrative, it was possible to rewrite the history of Portuguese Social Work, under a new perspective, showing not only the personal experience of those who describe it, but revealing institutions and people who are fundamental for the personal / professional maturation of the interviewees, as well as the Social Work in Portugal, a circumstance that touched on the relationship between Brazil and Portugal, solidified by Brazilian teachers and by PUC-SP. This thesis is the living memory; it is a tribute to the professionals and institutions that were fundamental in the constitution of the Portuguese Social Service. It is a memorial of the profession to perpetuate the history and memory of Social Work